Implementation of the Simple Additive Weighting (SAW) Method in a Decision Support System for Selecting the Chairperson of HIMA IFSI – S1 - Fikri Emsa Silmi; Pini Hasanah; Feri Alpiyasin (Politeknik Mardira Indonesia, 2026)
The selection of the Chairperson of Student Association (HIMA) is a crucial process in student organizations as it influences policy direction and organizational sustainability. However, in practice, the selection process is often influenced by subjective factors, resulting in suboptimal decisions. Therefore, a method is needed to assist in making objective and measurable decisions. This study aims to implement the Simple Additive Weighting (SAW) method in a Decision Support System (DSS) for selecting the HIMA IFSI S1 Chairperson at STMIK Mardira Indonesia. This research employs a quantitative approach with data obtained through questionnaires using a Likert scale of 1-5. Three HIMA Chairperson candidates were assessed based on five criteria: leadership, organizational experience, responsibility, communication skills, and vision and mission.